Phytochemical Profile and Comparative Anti-radical Scavenging Activities of n-Hexane Extracts of Indigenous Zingiber officinale and Curcuma longa - Nweze, Chibuzo Carole; Dingwoke, Emeka John; Adamude, Fatima Amin; Nwobodo, Nwobodo Ndubuisi (Free Radicals and Antioxidants)
Objectives: The therapeutic and nutritional values of plants and plant produce for aliment management and as food supplements are evolving. Free radical scavenging activities of n-haxane extracts of indigenous Curcuma longa and Zingiber officinale was investigated and compared to CellGevity®; a nutraceutical antioxidant supplement. In addition, their phytochemical profile was qualitatively and quantitatively determined using standard procedure for phytochemical analysis. Methods: The antioxidant activities of the extracts were determined spectrophotometrically. We used 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical, 2,2’-Azinobis3- ethylbenzothialine-6-sulfonic acid (ABTS) radical cations and hydrogen peroxide (H2O2) to determine free radical scavenging activities of the extracts. The ability of the extracts to scavenge free radicals was determined following the discoloration of the solution mixtures, measured spectrophotometrically. The reducing power efficacy of the extracts was determined by their ability to reduce Fe3+ to Fe2+ ions. Results: Curcuma longa and Zingiber officinale have more free radical scavenging power compared to CellGevity®. Curcuma longa has more scavenging power against DPPH and H2O2 system, while Zingiber officinale has more scavenging power against ABTS cations. CellGevity® had the least scavenging activity against the free radicals, as observed in this study. The highest phenolic, flavonoid, Vitamin C, Vitamin B1 and Vitamin B2 quantified were found in Curcuma longa and Zingiber officinale compared to CellGevity®. Conclusion: The indigenous Curcuma longa and Zingiber officinale are natural sources of effective antioxidants with more scavenging power compared to a standard CellGevity® nutraceutical.
Keywords: Oxygen-free radicals; Oxidative stress; Antioxidant; Curcuma longa; Zingiber officinale; Nutraceutical